ANALYSIS OF INCOME INEQUALITY (GINI RATIO) AND ITS IMPACT ON THE HUMAN DEVELOPMENT INDEX (HDI) IN WEST SUMATRA PROVINCE - Amaluis, Dina; Ronald, Jimi; Amelia, Mona; Stevani, Stevani; Syamra, Yesmira; Eprillison, Vivina (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2024)
This study aims to see or find out 1) the phenomenon of income inequality during 5 years of observation in the Districts / Cities of West Sumatra Province, 2) Human Development Index in Districts / Cities of West Sumatra Province, 3) The Impact of Income Inequality on the Human Development Index in Districts / Cities of West Sumatra Province, The type of research used is associative research. This research was conducted using the object of research in districts / cities in West Sumatra province consisting of 19 districts / cities in Sumatra Bara province. Research data used during the period 2017-2021 with 90 samples. The results showed that: 1) Income Inequality has a negative and significant impact on the Human Development Index in the Districts / Municipalities of West Sumatra Province.